Minding Glial Cells in the Novel Understandings of Mental Illness - Aye M. Myint (Frontiers Research Topics, 2017)
Traditionally, abnormalities of neurons and neuronal networks including synaptic abnormalities and disturbance of neurotransmitters have dominantly been believed to be the main causes of psychiatric disorders. Recent cellular neuroscience has revealed various unknown roles of glial cells such as astrocytes, oligodendrocytes and microglia. These glial cells have proved to continuously contact with neurons /synapses, and have been shown to play important roles in brain development, homeostasis and various brain functions. Beyond the classic neuronal doctrine, accumulating evidence has suggested that abnormalities and disturbances of neuron-glia crosstalk may induce psychiatric disorders, while these mechanisms have not been well understood. This Research Topic of the Frontiers in Cellular Neuroscience will focus on the most recent developments and ideas in the study of glial cells (astrocytes, oligodendrocytes and microglia) focusing on psychiatric disorders such as schizophrenia, mood disorders and autism. Not only molecular, cellular and pharmacological approaches using in vitro / in vivo experimental methods but also translational research approaches are welcome. Novel translational research approaches, for example, using novel techniques such as induced pluripotent stem (iPS) cells, may lead to novel solutions. We believe that investigations to clarify the correlation between glial cells and psychiatric disorders contribute to a novel understanding of the pathophysiology of these disorders and the development of effective treatment strategies.